Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,36.19+36.81\)
\(=36.\left(19+81\right)\)
\(=36.100\)
\(=3600\)
\(b,8.12.125.5\)
\(=\left(125.8\right)\left(12.5\right)\)
\(=1000.60\)
\(=60000\)
\(c,\)chịu
c,7 x 9 + 14 x 27 + 21 x 36 / 21 x 27 + 42 x 81 + 63 x 108
7 x 9 + 14 x 27 + 21 x 36 / 7 x 3 x 9 x 3 + 14 x 3 x 27 x 3 + 21 x 3 x 36 x 3
1 / 3 x 3 + 3 x 3 + 3 x 3
1 / 9 + 9 + 9
1 / 27
Ta có : \(\dfrac{3\left(\dfrac{1}{41}-\dfrac{4}{47}+\dfrac{9}{53}\right)}{4.\left(\dfrac{1}{41}-\dfrac{4}{47}+\dfrac{9}{53}\right)}=\dfrac{3}{4}\)
\(\dfrac{\dfrac{3}{41}-\dfrac{12}{47}+\dfrac{27}{53}}{\dfrac{4}{41}-\dfrac{16}{47}+\dfrac{36}{53}}\)
\(=\dfrac{3\times\left(\dfrac{1}{41}-\dfrac{4}{47}+\dfrac{9}{53}\right)}{4\times\left(\dfrac{1}{41}-\dfrac{4}{47}+\dfrac{9}{53}\right)}\)
\(=\dfrac{3}{4}\)
(-6,17 +3+5/9-2-36/97)*(1/3-1/4-1/12)=(-6,17+3+5/9-2-36/97)*(4/12-3/12-1/12)=(-6,17+3+5/9-2-36/97)*0=0
\(B=\frac{4^9.36+64^4}{16^4.100}\)
\(B=\frac{4^9.4.3^2+\left(4^3\right)^4}{\left(4^2\right)^4.4.5^2}\)
\(B=\frac{4^9.36+4^{12}}{4^8.4.5^2}\)
\(B=\frac{4^9.\left(36+64\right)}{4^9.25}\)
\(B=\frac{100}{25}\)( \(4^9\ne0\))
\(B=4\)
Tham khảo nhé~
a) \(125\cdot\left(-24\right)+24\cdot225\)
\(=\left(225-125\right)\cdot24\)
\(=100\cdot24\)
\(=2400\)
b) \(26\cdot\left(-125\right)-125\cdot\left(-36\right)\)
\(=\left(36-26\right)\cdot125\)
\(=10\cdot125\)
\(=1250\)
a) \(\frac{30}{51}\)\(-\)\(\frac{20}{52}\)\(+\)\(\frac{14}{34}-\frac{56}{91}-2\)
\(=\frac{10}{17}-\frac{5}{13}+\frac{7}{17}-\frac{8}{13}-2\)
= (\(\frac{10}{17}\)\(+\frac{7}{17}\)) \(-\)(\(\frac{5}{13}+\frac{8}{13}\)) \(-2\)
= \(1-1-2\)
=\(0-2\)
= -2
k cho mik nha
a) \(|3a-1|=|-14|\)
\(\Leftrightarrow|3a-1|=14\)
\(\Leftrightarrow\orbr{\begin{cases}3a-1=14\\3a-1=-14\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}a=5\\a=\frac{-13}{3}\end{cases}}\)
Vậy ..,.
\(b,-12\left|1-2a\right|=-36\)
\(\Rightarrow\left|1-2x\right|=-\frac{36}{-12}\)
\(\Rightarrow\left|1-2x\right|=3\)
\(\Rightarrow\orbr{\begin{cases}1-2x=3\\1-2x=-3\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x=-2\\2x=4\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=-1\\x=2\end{cases}}\)
\(125\left(-36\right)+\left(-36\right)\left(-52\right)+36\left(-27\right)+\left(-400\right)\)
\(=-36\left(125-52+27\right)+\left(-400\right)\)
\(=-36\cdot100-400\)
=-3600-400
=-4000
125(−36)+(−36)(−52)+36(−27)+(−400)
=−36(125−52+27)+(−400)
=−36⋅100−400
=-3600-400
=-4000